Effect of plant density on yield and physiological characteristics of six canola cultivars - Nasiri, Anaz; Samdaliri, Morteza; Shirani Rad, Amirhossein; Shahsavari, Nasser; Mosavi Kale, Amirabbas; Jabbari, Hamid (Journal of Scientific Agriculture, 2017)
An experiment was performed in the Seed and Plant Improvement Institute, Karaj, Iran to study the influence of plant densities on physiological traits of six canola cultivars. Treatment conditions included three different plant densities (40, 60, and 80 plants m-2) for triplicates of six canola cultivars, namely, Ahamadi, Opera, Okapi, L72, Karaj1, and Sw102. Results indicated that L72 cultivar exhibited the highest yield at the lowest plant density (40 plants m-2). For all cultivars, both plant densities of 60 and 80 plants m-2 resulted in lower relative water content than 40 plants m-2. Proline and carbohydrate content significantly increased with increasing plant densities. The highest proline content was obtained from L72 under the highest plant density, whereas the lowest was also detected in this cultivar at the lowest plant density. All cultivars grown at the lowest density showed higher amounts of photosynthetic pigments chlorophylls a and b than those at the highest density. Glucosinolate increased with increasing plant densities, with L72 yielding the highest quantity when grown at the highest density. In conclusion, a density of 40 plants m-2 is recommended for growing L72 in this region.